A Taxonomy of Legal Control. Issue 2 (3rd August 2018) - Ward, Daniel
Abstract : Ideas as to how the law exercises control over its subjects can be formulated as explanations for the concurrence of two facts: A. the law stipulates certain behaviour, and B. a given subject behaves in conformity with that stipulation. Such explanations can be organised into a taxonomy. The exercise forces us to consider what is important in a theory of legal order. The taxonomy developed here suggests that there are three main mechanisms for controlling a particular subject's behaviour: (1) collateral motivation (coercion and reward); (2) authority; and (3) coordination, or the intervention in the subject's strategic situation through affecting the behaviour of others. Other accounts have tended either to leave out coordination or to seek to assimilate it to authority. Such treatment overlooks important, ethically distinctive features of coordination as a mechanism of bringing about compliance with the law.